Estudo clínico longitudinal de dentes restaurados com sistemas cerâmicos livres de metal: estudo prospectivo sobre a hipersensibilidade dental pós-operatória - Souza, Fernando Isquierdo de [UNESP] (2014)
Objective: Considering the importance of post-operative dental hypersensitivity in clinical success of ceramic restorations in the short-term and the influence of the marginal integrity and the cementing line in the longitudinal results in this type of restoration, the aim of this clinical study is to evaluate the occurrence of post-operative hypersensitivity of teeth restored with metal-free ceramics, with the use of stimulating device temperature and verification of marginal integrity of cementation line with the scanning Electron Microscope (SEM). Materials and Methods: In the first chapter, 28 metal free restorations were installed, being 15 with Rely X Veneer (RV), 13 with Variolink Veneer (VV), cemented according to a Split-mouth design clinical trial model. The restored teeth were subjected to sensitivity threshold test by the cold sensation through the stimulator TSA II apparatus before the restorative procedure (baseline) and after 5 times of analysis [24h after cementation (t0 ) 7 days after t0 (t1) 15 (t2), 30 (t3), 60 days after t0 (t4)]. In the second chapter, 62 teeth were restored, being: 32 with RV, 30 with VV, according to a randomized clinical trial based in Split-mouth design. 19 crows were cemented with Rely X U200 [U]. The marginal integrity of ceramic restoration and the cementation line was evaluated in SEM and a clinical assessment based on modified criteria of the USPHS (United States Public Health Service) was performed at the times [t0 (day cementation), 30 (t1) and 180 days after t0 (t2)]. Results: Quantitative sensory testing found no increase in tooth sensitivity after installation of restorations in any of the experimental groups (p <0.05). However, 57,2% of patients reported postoperative dental hypersensitivity in eating habits on 30-day control. For teeth evaluated in the second stage of the study, 58.02% presented with horizontal...